DETEKSI DINI PENYAKIT JANTUNG KORONER DENGAN PEREKAMAN ELEKTROKARDIOGRAM DI RT 04 RW 01 , KELURAHAN 5 ILIR, KECAMATAN IT II KOTA PALEMBANG - Sukma Wicaturatmashudi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Coronary heart disease is a degenerative disease that increases in incidence as a person ages. This disease often appears asymptomatic and life-threatening at the onset of the attack. The aim of this community service is to increase citizens' knowledge about coronary heart disease and early detect the risk of coronary heart disease. The method used in this community service activity is to conduct education and examination of ECG recording. The number of residents who participated was 15 people with the youngest 50 years old and the oldest 81 years old. The results of community service were analyzed in a narrative manner and showed that 9 people were categorized as hypertension. Based on the results of the ECG recording, 13 residents had abnormal ECG rhythms and 9 of them have the rhythm criteria for patients with coronary heart problems. For residents whose ECG rhythm is not normal, it is recommended to carry out further tests to ensure their heart condition and to manage it quickly and accurately.